IMPLEMENTASI PROGRAM DESA DALAM PENGELOLAAN SAMPAH DI DESA BUTUH KECAMATAN MOJOSONGO KABUPATEN BOYOLALI - Faridah Az Zahro; Ari Subowo; Teuku Afrizal (Journal of Public Policy and Management Review, 2022)
Waste management is one of the village programs chosen by the Village Government to overcome the problem of waste whose volume has increased. This study aims to describe and analyze the implementation of village programs in waste management in Butuh Village, Mojosongo District, Boyolali Regency and the factors that influence it using George C. Edwards III's theory, namely communication, resources, disposition, and bureaucratic structure. This research method uses descriptive qualitative research with village heads, waste managers, RT heads, business actors, and the community as informants. The results of the study indicate that the implementation of the village program in waste management in Butuh Village has been going well but has not been maximized. The influencing factors include the lack of human resources in terms of community participation, the absence of physical facilities for waste storage in each RT. Then at the disposition there is no incentive for waste management in Dusun 1 due to the rising cost of transporting waste. Suggestions for the village government are increasing socialization and education to the community, realizing the provision of garbage containers as physical facilities in each RT, allocating sources of funds from the village for the cost of transporting waste from Dusun 1 TPS to TPA. In addition, the community is expected to apply village regulations and participate in program implementation.